PENGARUH LAMA PERENDAMAN DALAM LARUTAN KAPORIT DAN KONSENTRASI ASAM SITRAT TERHADAP MUTU PEKTIN CAIR KULIT PISANG KEPOK - Miranti Miranti; Mahyu Danil (Universitas Quality, 2018)
Indonesia is an agricultural country where most of the farmers grow fruits andvegetables. Each harvest of harvests will leave a part that is considered to have noeconomic value anymore. This part is known as waste. Agricultural waste can be in theform of fruit peels, fruit flesh (which is taken by seeds), leaves, stems and so on. Alongwith technological advancements, starting with the utilization of waste with the properapplication of technology, will be able to raise the value of waste. The abundance ofbanana production in Indonesia shows that, throughout the year there will be abundantavailable banana waste, in the form of banana peels, banana flowers (heart), or bananastem stumps. Banana peel pectin is one of the products produced by banana peels thatare not yet known in the Indonesian community. Pectin can be extracted from the residueof fruit processing, such as orange peel, the rest of the making of apple juice, coconutfiber, banana peel, brown skin and others. The content of pectin in various fruits variesgreatly. In fruits of different varieties the pectin content will differ. The banana peelwaste which is around 62-67% of the total weight, can be used as a source of pectin. Ifthe skin of a banana is used as a source of producing pectin, it will be one of the wasteutilization businesses, as well as an effort to develop industries, especially smallindustries in the supply of pectin, which is currently still expensive with such a large use.Solving or extracting pectin from fruits is affected by cooking and pH of the solution.Research Methods: The design model used in this study is factorial randomized completedesign (RAL), which consists of two main factors, namely: Factor I: Immersion Length inChlorine Solution (P) consisting of 4 levels: P1 (1 min), P2 (3 min), P3 (5 min), P4 (7min). Factor II: Citric Acid Concentration (K) consisting of 4 levels: K1 (1.5%), K2(2.0%), K3 (2.5%), K4 (3.0%). The study used 2 replications. The results of the studygenerally indicate that the effect of immersion time in chlorine solution and theconcentration of citric acid on the quality of the liquid pectin of kepok banana influencesthe observed parameters. The best crude pectin content is 2.039% (7 min) and 2.604%(3.0%). The best methoxyl content is 3.930% (7 min) and 5.210% (3.0%). The best jellygrade is 299,254 (7 min) and 299,445 (3.0%). The best thickness is 1.036 (7 min) and1.045 (3.0%).